Milk flavor unaffected by Plastic Baler Twine - T Nickerson; R Baldwin (California Agriculture, 1965)
Consumption of significant quantities of shredded plastic (polypropylene) baler twine had no effect on animal performance or milk flavor, in this short-term trial with dairy cattle.